Evaluation Study of the High Yielding Varieties Programme Kharif-1967 First Report - Planning Commission (Planning Commission, 1968)
A new phase in Indian agriculture began with the launching of the High Yielding Varieties Programme in 1966-67. The scientific revolution centred around the dwarf varieties of paddy and wheat responsive to higher doses of fertilisers compared to the varieties in vogue in the country so far. Extending cultivation of these and other hybrid varieties over large areas implied tremendous organisational and promotional efforts at least in the initial years. Drawing upon the experience gained in the course of two current appraisals carried out by the P.E.O. during the Rabi, 1965-66 and the Kharif of 1966, it was considered desirable to conduct a detailed field investigation on the H.V.P., so as to establish firm base line data in the initial years. This is the first report based on such a detailed field study undertaken by the P.E.O. during the kharif, 1967. In this study, aspects relating to planning, programming, organisation of input supplies, extent of adoption of practices by participants and problems of non-participants are covered.
Programme Evaluation Organisation Planning Commission Government of India